PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR IPA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) - Anna Prianti; Hidayati Hidayati; Tias Ernawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
The objective of this study was to improve students’ activity and science learning achievement  at VIII B grade students through a learning model Cooperative Integrated Reading and Composition (CIRC) in SMP N 4 Banguntapan Bantul in academic year 2014/2015. This study belongs to Classroom Action Research (CAR). Observation, test, and documentation were used to gather the data in this study. The results of the study showed that after implementing the Cooperative Integrated Reading and Composition (CIRC) model at VIII B class in SMP N 4 Banguntapan Bantul, students’ activity and learning achievement increased. It was shown by the increase of students’ percentage in observation sheets in each cycle. It is proven by the enhancement of average percentage of student liveliness observation worksheet for each cycle; the average of activity indicator in cycle 1 is 70,37%. It increased 20,98% to 91,35% in cycle 2. The average learning outcomes of science in pre-action was 52,1 increased to 56,64 in cycles 1 and 81,28 in cycle 2. The numbers of student that passed the passing grade in the pre-action were 6 students with a percentage of 22,22%. In cycles 1, it increasesd to 48,15% with 13 students passed the passing grade and it becqmee 85,19% in cycles 2 with 23 students. Based on the result of research conducted, the researcher advices science teacher to apply peer teaching as a variation of the learning model.